Spatial and temporal development of phytoplankton iron stress in relation to bloom dynamics in the high‐latitude North Atlantic Ocean. (9th February 2013) - Ryan-Keogh, Thomas J.; Macey, Anna I.; Nielsdóttir, Maria C.; Lucas, Michael I.; Steigenberger, Sebastian S.; Stinchcombe, Mark C.; Achterberg, Eric P.; Bibby, Thomas S.; Moore, C. Mark
Abstract : The high‐latitude North Atlantic (HLNA) is characterized by a marked seasonal phytoplankton bloom, which removes the majority of surface macronutrients. However, incomplete nitrate depletion is frequently observed during summer in the region, potentially reflecting the seasonal development of an iron (Fe) limited phytoplankton community. In order to investigate the seasonal development and spatial extent of iron stress in the HLNA, nutrient addition experiments were performed during the spring (May) and late summer (July and August) of 2010. Grow‐out experiments (48–120 h) confirmed the potential for iron limitation in the region. Short‐term (24 h) incubations further enabled high spatial coverage and mapping of phytoplankton physiological responses to iron addition. The difference in the apparent maximal photochemical yield of photosystem II (PSII) (Fv : Fm ) between nutrient (iron) amended and control treatments (Δ(Fv : Fm )) was used as a measure of the relative degree of iron stress. The combined observations indicated variability in the seasonal cycle of iron stress between different regions of the Irminger and Iceland Basins of the HLNA, related to the timing of the annual bloom cycle in contrasting biogeochemical provinces. Phytoplankton iron stress developed during the transition from the prebloom to peak bloom conditions in the HLNA and was more severe for larger cells. Subsequently, iron stress was reduced in regions where macronutrients were depleted following the bloom. Iron availability plays a significant role in the biogeochemistry of the HLNA, potentially lowering the efficiency of one of the strongest biological carbon pumps in the ocean.